(untitled) (Journal of the College of Education for Women, 2019)
The person who wants to learn. The history of Bab’is will notice a verystarnge phenomenon that they (Babis and Baha’is) resort to visions to prove theirdelusion.The believers usually reach to each other by their visions. This phenomenonare shared among them from Al- Ahsa’ai time till the last phase of their propagandawhich is the Baha’is propaganda, and this is due to their ignorance and underdevelopment in doctrine of islam which was widespread in Iran and the Islamic world.The whole secrets of Babis and Baha’is movement were restricted amongparticular group, most of them were Al- Rashti’s students and knew the basicprinciples of their movement which deperding or (the principles) declaration of oldinternal opinions, leaving the Islamic worhips and distort sharia. Besides the role ofthe colonial countries, those put the plans to destroy the Islamic religion, they havethe wapper and stronger hand in supporting and this movement with money andweapons and establishing it. So the Baha’is movement considered the higher stage inthe historical plot stages against Islam, beginning with internal magicians and endingwith internal modern which directed by the christianity preachers systems and theglobal zionism Masony systems.